Diagnostic value of third-generation nanopore sequencing in extrapulmonary tuberculosis - Song, Chang; Zhao, Chunyan; Lin, Yanrong; Nong, Yingxing; Huang, Aichun; Xi, Shaoyong; Wei, Xiaoying; Zeng, Chunmei; Yang, Shixiong; Zhu, Qingdong (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThis study aimed to explore the accuracy of third-generation nanopore sequencing to diagnose extrapulmonary tuberculosis (EPTB).MethodsSamples were collected from the lesions of 67 patients with suspected EPTB admitted between April 2022 and August 2023. Nanopore sequencing, acid-fast bacilli (AFB) staining, DNA testing, and X-pert and mycobacterial cultures were performed. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and area under the receiver operating characteristic curve (AUC) were calculated for different diagnostic methods, and their diagnostic accuracies were compared.ResultsNanopore sequencing demonstrated the highest correct diagnosis rate among 50 positive EPTB cases, independently diagnosing 19 positive cases missed by conventional methods. Its sensitivity (62.00%), specificity (94.10%), PPV (96.90%), NPV (45.70%) and AUC (0.781, 95% CI: 0.67–0.89) were superior to those of conventional methods, such as AFB staining, DNA testing, X-pert, and solid culture, indicating its significantly efficient advantage in EPTB detection.ConclusionNanopore sequencing technology significantly outperforms conventional methods such as AFB staining, DNA testing, X-pert, and mycobacterial culture to diagnose EPTB, promising to improve the diagnosis of EPTB.